Partial Productivity Analysis of Production Divisions By Omax Method - Setyadi, Antonius (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aimed to analyze the production department’s partial productivity measurement using the Objective Matrix (OMAX) method at PT. GMK. The OMAX method's key performance indicators (KPIs) affecting the productivity index must be defined and weighted for each criterion using the Analytical Hierarchy Process (AHP). The study was conducted in the production division of PT. GMK, which produces compound chocolate. The results showed that the productivity of was affected by the partial productivity of raw materials and labor and the electric power’s effectiveness. Other factors were the minimization of overtime working hours, labor costs, downtime, as well as defective and semi-finished products. Moreover, this study determined the standard performance in the second semester of 2021. It also conducted a causal analysis using a fishbone diagram to find the cause of employees’ low productivity. The analysis showed that the average productivity index increased between January and August 2022.